A MULTIMODAL ANALYSIS ON ENVIRONMENTAL POSTERS IN THE SELECTED GREENPEACE POSTERS CAMPAIGN - Afrida Fitriyani Sipahutar (English Language Teaching Prima Journal (ELT), 2022)
Exposure of environmental issues is essential to prevent mass environmental destructions; therefore, campaigns (posters) should be able to activate the viewers’ contemplation on such issues. Accordingly, this study focuses on the interactive meanings of semiotic resources in posters on environmental campaigns using a multimodal perspective. The study aims to find out the visual and verbal elements in environmental posters in selected Greenpeace poster campaigns. The research method used in this study was a descriptive qualitative method proposed by Miles and Huberman. The result of the research revealed that verbal and visual elements in Greenpeace poster included caption and images. Verbal elements were analyzed in the term of Transitivity analysis by using Halliday’s SFL. Visual elements were analyzed in three pattern of Kress Van Leuwen’s Grammar Visual Design. The verbal and visual elements created meaning by relating to each other and supported each other. Similar represented participants and processes were visually found as well as verbally participants and process. Mostly, the meaning of the Greenpeace poster invites the readers to take any action in protecting nature.   Keywords: Multimodal, verbal and visual elements, environmental awareness.